1972
DOI: 10.1055/s-0028-1094113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epinephrine and Norepinephrine on the Hepatic Lipids of the Nurse Shark, Ginglymostoma cirratum

Abstract: The lipid and fatty acid composition and the effect of epinephrine and of norepinephrine upon acetate-I-14 C incorparation into liver lipids were studied in the nurse shark. The total lipid content varied between 3.5 and 12.8% of the fresh weight of the organ, an amount significantly lower than that found in the liver of other elasmobranchs. The triglycerides represented about 60% and the phospholipids about 10% of the total extractable lipids, whereas in mammals, these fractions represent 30% and 65% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…The hormone seemed to be without effect in European eel (Larsson & Fiinge 1977). Corticosterone favours the mobilization of fat in the liver of shark and cortisol, in chimaera (Patent 1970, Lipshaw et al 1972. The same effect, stimulation of lipolysis, was observed after repeated injections of corticosteroids in mammals (Steinberg 1963, Mosinger 1968.…”
Section: Hormonal Treatmentmentioning
confidence: 58%
See 1 more Smart Citation
“…The hormone seemed to be without effect in European eel (Larsson & Fiinge 1977). Corticosterone favours the mobilization of fat in the liver of shark and cortisol, in chimaera (Patent 1970, Lipshaw et al 1972. The same effect, stimulation of lipolysis, was observed after repeated injections of corticosteroids in mammals (Steinberg 1963, Mosinger 1968.…”
Section: Hormonal Treatmentmentioning
confidence: 58%
“…Some authors have confirmed the lipolytic effect of catecholamines in rainbow trout and eel (Mazeaud 1969, Larsson 1973) and observed marked mobilization of lipid stores in liver of elasmobranchs (Patent 1970, Lipshaw et al 1972. In other cases investigators when studying representatives of different fish species, mainly cyprinids, after the epinephrine administration detected, like Farkas, a decrease of PFA level developed in parallel with hyperglycaemia (Mazeaud 1969, Minick & Chavin 1969, Ince & Thorpe 1975.…”
Section: Hormonal Treatmentmentioning
confidence: 75%
“…Administration of noradrenaline to carp led to a decrease in plasma NEFA concentrations in vivo and a similar decrease in NEFA concentrations from adipose tissue in vitro (Farkas 1969). Furthermore, noradrenaline decreased acetate incorporation into hepatic lipids indicating additional metabolic effects of catecholamines on fish liver (Lipshaw, Patent & Foa 1972). Increased plasma NEFA concentrations have been reported in lamprey and eel following catecholamine treatment (Plisetskaya 1980;Larsson 1973), while noradrenaline was shown to induce liberation of NEFA in isolated salmon hepatocytes (Sheridan 1987).…”
Section: Demonstrated Thatmentioning
confidence: 85%
“…The two study species (tiger and bull shark) that usually have the most generalist diet within the group of species investigated (Cortés, 1999) had the lowest TAG. High concentrations of TAG are found in the livers of many species of shark (Lipshaw et al ., 1972; Pethybridge et al ., 2011; Beckmann et al ., 2013a, b), and TAG is typically bound to lipoproteins when circulating in the blood (Mills et al ., 1977). It is possible that the low TAG concentrations found here could be attributed to the consumption of a broad diet of both high- and low-quality nutritional items.…”
Section: Discussionmentioning
confidence: 99%